Climate Coalitions: A Theoretical and Computational Appraisal - Thierry Bréchet; François Gerard (Fondazione Eni Enrico Mattei (FEEM), 2007)
Using an updated version of the CWS model (introduced by Eyckmans and Tulkens in Resource and Energy Economics 2003), this paper intends to evaluate with numbers the respective merits of two competing notions of coalition stability in the standard global public goods model as customarily applied to the climate change problem. After a reminder of the model structure and of the definition of the two game theoretical stability notions involved namely, core stability and internal-external stability, the former property is shown to hold for the grand coalition in the CWS model only if resource transfers of a specific form between countries are introduced. It is further shown that while the latter property holds neither for the grand coalition nor for most large coalitions, it is nevertheless verified in a weak sense that involves transfers (dubbed potential internal stability) for most small coalitions. The reason for this difference is brought to light, namely the differing rationale that inspires the transfers in either case. Finally, it is shown that the stable coalitions that perform best (in terms of carbon concentration and global welfare) are always composed of both industrialized and developing countries. Two sensitivity analyses confirm the robustness of all these results.
Keywords: C71; C73; D9; D62; F42; Q2; 330; Climate Change; Coalitions; Simulation; Integrated Assessment